As contribuições da retextualização para o trabalho com o artigo de opinião nos anos iniciais do Ensino Fundamental - Rodrigues, Teodora da Silva (2024)
Although the opinion piece is a speech genre listed in Base Nacional Comum Curricular – BNCC (Brasil, 2018), it seems to be more widely studied in the late grades of elementary school and in high school than in the early grades of elementary school. Experience shows that teachers prefer teaching text types (such as narrative or descriptive text) to the study of genre, mainly the argumentative ones, in the early grades of elementary school. This may be the reason why students of the late grades of elementary school find it hard to understand and write argumentative text. In this context, this research aimed at addressing opinion piece as speech genre by means of retextualization of news, enabling students to properly understand and write an opinion piece. The research was conducted with 17 fifth-grade students (eleven of which participated actively in the study) from a public school in Santa Maria (DF). The methodology was grounded in the principles of action research and qualitative data analysis. The action research involved educational workshops as a teaching strategy. Highlighting text and genre as core concepts to Portuguese language teaching, this research resonates with similar studies that support interactive learning based on the plurality of discourse. It also considers opinion pieces and news to be part of the daily life of students and retextualization as a habit in social discourse practice. The assignment that is proposed in this research put students in contact with different opinion pieces and news. It helped students to broaden what they know about the genre and improve their arguing skills. Considering the objectives, this research drew on authors who deal with text and discourse concerning the teaching of Portuguese language, such as Dell’Isola (2007), Geraldi (1993, 2010, 2012), Koch (1987, 2016), and Marcuschi (2008, 2010). Based on the literature, an assignment on retextualization strategy was proposed. The research also developed a handbook for approaching retextualization workshop in fifth-grade class. This handbook is intended to provide fifth-grade class teachers with a teaching resource which helps them run workshops on writing skills development. It is believed to contribute to teaching practice regarding strategies for coping with writing and re-writing challenges students face. Once the assignment was finished, results were analysed. The activity was checked against the objectives, to assess the need for adjustments. The results show that most of students were able to understand the process for retextualizing news into opinion pieces, allowing for different assignments on text and discourse. The educational workshops proved to be effective in teaching Portuguese language, since they cover many instances of social interaction. Finally, this research is expected to help both Portuguese language teachers to plan classes in opinion piece to the early grades of elementary school and students to develop their discourse skills, argumentation, critical thought, and decision making wherever they live.